DEVELOPMENT GUIDELINES FOR STUDENT TEACHERS WITH A NETWORK OF SCHOOLS THROUGH AN EDUCATIONAL SUPERVISION SYSTEM, MAHACHULALONGKORNRAJAVIDYALAYA UNIVERSITY, NAKHON SI THAMMARAT CAMPUS - Hanthet, Sakda; Prabparn, Anuchid; Chantra, Tippawan (Journal of MCU Nakhondhat, 2023)
Developing the quality of teachers is an important part of educational development. Improving the quality of teachers not only provides good education, but also promotes important skills and knowledge necessary for future professional teaching careers. One way to achieve this is to provide professional teaching experience in educational settings. Professional teaching experience is an important component of vocational education and allows students to apply theoretical knowledge in real-world situations. This hands-on experience is crucial in preparing students for real-life situations in future teaching careers. However, teachers in training may face unexpected problems during their teaching experience, and it is important to provide guidance and support to prevent them from feeling isolated. Therefore, each curriculum is designed to provide guidance and counseling to students, creating a mentoring system. The mentoring system helps students plan their learning strategies, design teaching methods, and provide guidance in teaching, school management, and other areas. It is evident that the mentoring system is of great importance due to the variety of problems that may arise in different educational contexts. The mentoring system helps to develop students' skills and knowledge and each mentoring session demonstrates the continuous improvement of students' learning and other skills, based on feedback and suggestions from relevant stakeholders.